Customer Satisfaction Index (CSI) dan Importance-Performance Analysis (IPA) sebagai Alat Ukur Layanan pada Pelabuhan - Rayyan Dzikru Huwaiza; Rubby Rahman Tsani; Melia Handayani (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
This study aims to analyze customer satisfaction with ferry crossing services at PT ASDP Indonesia Ferry (Persero) Merak Branch using the Customer Satisfaction Index (CSI) and Importance–Performance Analysis (IPA) methods. Increasing passenger and vehicle mobility on the Merak–Bakauheni route requires continuous improvement in service quality to meet customer expectations. This research employed a descriptive quantitative approach by distributing structured questionnaires to ferry service users. The questionnaire measured the level of importance and performance of service attributes using a Likert scale. Data were analyzed using CSI to determine the overall level of customer satisfaction and IPA to identify priority service attributes for improvement and maintenance. The study involved ferry service users who had utilized the service at least twice, and data collection was conducted at Merak Port. The results indicate that the customer satisfaction index is in the moderate category, implying that service performance has not fully met customer expectations. IPA mapping shows that cleanliness and adequacy of facilities, waiting room comfort, and clarity of departure information fall into Quadrant I and require immediate improvement. Meanwhile, ticketing speed, staff friendliness, and passenger safety are located in Quadrant II and should be maintained. These findings provide practical implications for service providers to improve facilities, optimize information systems, and enhance staff performance to increase customer satisfaction and loyalty.optimization, and continuous staff development to improve customer satisfaction and loyalty